Antifungal activity of Co(II) and Cu(II) complexes containing 1,3-bis(benzotriazol-1-yl)-propan-2-ol on the growth and virulence traits of fluconazole-resistant Candida species: synthesis, DFT calculations, and biological activity - Ricardo A. Murcia-Galán; Sandra M. Durán; Sandra M. Leal-Pinto; Martha V. Roa-Cordero; Jose D. Vargas; Laura V. Herrera; Alvaro Muñoz-Castro; Desmond MacLeod-Carey; Tonny W. Naranjo; Peter L. Rodríguez-Kessler; John J. Hurtado (BMC Chemistry, 2023)
Abstract Relevant virulence traits in Candida spp. are associated with dimorphic change and biofilm formation, which became an important target to reduce antifungal resistance. In this work, Co(II) complexes containing a benzotriazole derivative ligand showed a promising capacity of reducing these virulence traits. These complexes exhibited higher antifungal activities than the free ligands against all the Candida albicans and non-albicans strains tested, where compounds 2 and 4 showed minimum inhibitory concentration values between 15.62 and 125 μg mL−1. Moreover, four complexes (2–5) of Co(II) and Cu(II) with benzotriazole ligand were synthesized. These compounds were obtained as air-stable solids and characterized by melting point, thermogravimetric analysis, infrared, Raman and ultraviolet/visible spectroscopy. The analysis of the characterization data allowed us to identify that all the complexes had 1:1 (M:L) stoichiometries. Additionally, Density Functional Theory calculations were carried out for 2 and 3 to propose a probable geometry of both compounds. The conformer Da of 2 was the most stable conformer according to the Energy Decomposition Analysis; while the conformers of 3 have a fluxional behavior in this analysis that did not allow us to determine the most probable conformer. These results provide an important platform for the design of new compounds with antifungal activities and the capacity to attack other target of relevance to reduce antimicrobial resistance.